Human Work Interaction Design: Usability in Social, Cultural and Organizational Contexts Second IFIP WG 13.6 Conference, HWID 2009, Pune, India, October 7-8, 2009, Revised Selected Papers - Katre, Dinesh; Orngreen, Rikke; Yammiyavar, Pradeep; Clemmensen, Torkil; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the Second IFIP WG 13.6 International Conference on Human Work Interaction Design, HWID 2009, held in Pune, India, in October 2009. The 20 revised papers presented were carefully selected from numerous submissions. The papers are organized in topical sections on usability in cultural context; internationalization and localization of usability; usability in social context; and usability in organizational context.
Usability in a Cultural Context: A Report on the Scope, Process and Research Results of CultUsab - The Cultural Usability Project -- Status of HCI and Usability Research in Indian Educational Institutions -- Usability in Cultural Contexts -- A Comparison of What Is Part of Usability Testing in Three Countries -- Augmenting Usability: Cultural Elicitation in HCI -- Exploring Persona-Scenarios - Using Storytelling to Create Design Ideas -- Usability and Culture as Two of the Value Criteria for Evaluating the Artifact -- Personas in Cross-Cultural Projects -- Usability Heuristics and Qualitative Indicators for the Usability Evaluation of Touch Screen Ventilator Systems -- An Overview of a Decade of Journal Publications about Culture and Human-Computer Interaction (HCI) -- Internationalization and Localization of Usability -- Analyzing Cultural Usability of Mobile Keypad and Displays for Textual Communication in Internationalization and Localization Perspectives -- Design of a Template for Handwriting Based Hindi Text Entry in Handheld Devices -- Development of an Intuitive User-Centric Font Selection Menu -- Usability in Social Contexts -- Interaction Design and Usability of Learning Spaces in 3D Multi-user Virtual Worlds -- Identifying the Cognitive Needs of Visitors and Content Selection Parameters for Designing the Interactive Kiosk Software for Museums -- Case Study of Online Banking in India: User Behaviors and Design Guidelines -- One-Handed Thumb Use on Smart Phones by Semi-literate and Illiterate Users in India -- Usability in Organizational Contexts -- Developing a Mobile Phone Based GUI for Users in the Construction Industry: A Case Study -- Usability Considerations in Developing a Graphic Interface for Intra Office Communications -- Interaction Design as a Multimodal Conversation.
Keywords: Computer science; Humanities; Computer Science; Computers and Society; User Interfaces and Human Computer Interaction; Media Design; Personal Computing; e-Commerce/e-business.; Cultural Heritage